Measuring Inequality of Access : Modeling Physical Remoteness in Nepal - Banick, Robert; Kawasoe, Yasuhiro (World Bank, Washington, DC, 2019)
Simple linear distances between origin and destination poorly describe travel in Nepal, where rugged terrain, underdeveloped transportation infrastructure, and diverse vegetation heavily influence favorable travel routes. In this context, expected travel times explain more about the remoteness of starting locations than geographic distance. Applied to service facilities, these time‐based measures of remoteness amount to measures of physical accessibility to services. However, traditional survey‐based measures of time suffer from problems of inaccurate reporting and standard survey error. Instead, this study built a geographic information system–based cost time model of travel that enables more accurate and generalizable assessment of accessibility. Having validated the generic model and compared it with other popular metrics, the study demonstrates its value by inputting a variety of services into it. This paper provides descriptive analyses of accessibility trends to these services at national, provincial, municipal, and geographic scales and suggests research possibilities unlocked by such a general purpose model. The paper concludes with thoughts for how the data and analysis, both freely available public goods, can enable additional research and better policy making.